Brief research report: OM-85 reduces SARS-COV-2 viral RNA expression in nasopharyngeal cells from COVID-19 patients - Cassão, Gisele; Antunes, Krist Helen; Gonçalvez, João Ismael Budelon; Santos, Leonardo Duarte; Abbadi, Bruno Lopes; Bizarro, Cristiano Valim; Machado, Pablo; Basso, Luiz Augusto; Pasquali, Christian; Stein, Renato T.; de Souza, Ana Paula Duarte (Frontiers in Virology, 2023)
OM-85 is a bacterial lysate from common respiratory tract pathogens, with an excellent safety profile, widely used to prevent recurrent respiratory tract infections. Several studies have been reporting the immunomodulating properties and antiviral roles of OM-85. The COVID-19 pandemic, originating in 2019, has presented a significant global public health crisis. While effective vaccines have been developed, vaccination rates vary considerably, and numerous concerning viral variants continue to emerge. The challenge persists in creating early interventions to halt the progression of the disease to its severe stages. To examine the therapeutic effect of OM-85 after SARS-CoV-2 infection and compared to recombinant human (rhINF-) we collected nasopharyngeal cells from COVID-19 patients. The cells were treated ex-vivo with OM-85 or hrINF- and the response was analyzed after 24h for gene expression by real-time PCR. We found that OM-85 decreased the SARS-CoV-2 N1 gene expression and increased RIG-I (DDX58) in these cells. The expression of ACE2 was undetected in these samples. These data support the antiviral effect of OM-85 against SARS-CoV-2.